The Effect of Employee Empowerment and Work Environment on Organizational Commitment and Their Impact on Employee Performance - Angelica Caroline Dwiputri; Oey Hannes Widjaja; Hadi Cahyadi; Henryanto Wijaya (International Journal of Application on Economics and Business, 2023)
This research was triggered by educational institutions in Indonesia that are not widely known by people out there. Education is a very common need and demand in children's lives. The purpose of education is to guide all the natural forces that exist in these children, so that they as humans and as members of society can achieve the highest safety and happiness. Education is also a conscious effort to prepare for the role of students in the future through guidance activities, such as counseling, education, and/or training. This study uses Structural Equation Modeling (SEM) to perform data analysis. The research sample consisted of 100 employees in private schools in North Jakarta. The results show that we must pay attention to the empowerment, environment, commitment and performance of employees who work in the field of education so that the future of the nation's children can be better than now.